How Tongxie-Yaofang Regulates Intestinal Synaptic Plasticity by Activating Enteric Glial Cells and NGF/TrkA Pathway in Diarrhea-Predominant Irritable Bowel Syndrome Rats - Lu X; Zhang S (Dove Medical Press, 2023)
Xiaofang Lu, Shengsheng Zhang Center of Digestive, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Shengsheng Zhang, Center of Digestive, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of China, Tel/Fax +86-10-87906634, Email zhangshengsheng@bjzhongyi.comPurpose: Diarrhea-predominant irritable bowel syndrome (D-IBS) is a frequent functional gastrointestinal disease that affects health and quality of life owing to its high incidence and recurrence rate. Tongxie-Yaofang (TXYF) is a traditional Chinese medicine prescribed for D-IBS. However, the therapeutic mechanism of TXYF has not been fully elucidated. This study aimed to investigate the effects of TXYF on visceral hypersensitivity in stress-induced D-IBS rats and the underlying mechanisms.Methods: Electromyographic (EMG) activity of the external oblique muscles and the abdominal withdrawal reflex (AWR) score captured by Barostat were used to quantify the effect of TXYF on visceral sensitivity. Transmission electron microscopy (TEM) was used to observe the ultrastructure of the enteric nervous system (ENS). For molecular detection, the colonic expression of enteric glial cell's (EGC's) activation markers, glial fibrillary acidic protein (GFAP) and calcium-binding protein S100β, NGF, TrkA, synaptic plasticity-related factors, synaptophysin (SYN) and postsynaptic density-95 (PSD-95), glutamate, glutamate receptors α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (AMPAR), and N-methyl-D-aspartate receptor (NMDAR) were detected by immunohistochemistry, enzyme-linked immunosorbent assay, and real-time PCR. An ex vivo experiment was conducted to measure the EGC-induced NGF release.Results: TXYF decreased the EMG activity and AWR scores in rats with D-IBS. Under TEM, TXYF improved the dense and irregular nerve arrangement, narrowed the synaptic cleft, and decreased the number of synaptic vesicles in D-IBS rats. In addition, TXYF decreased the expression of GFAP, S100β, SYN, and PSD-95; down-regulated the levels of NGF, TrkA, and glutamate; and reduced the mRNA expression of AMPAR1, NMDAR1, and NMDAR2B. In an ex vivo experiment, TXYF decreased NGF release in D-IBS rats, and this trend disappeared under EGC inhibition.Conclusion: TXYF alleviated visceral hypersensitivity in D-IBS rats possibly by improving synaptic plasticity through inhibiting the activity of EGCs and the NGF/TrkA signaling pathway in the colon.Keywords: diarrhea-predominant irritable bowel syndrome, Tongxie-Yaofang, visceral hypersensitivity, synaptic plasticity, enteric glial cell